ELF/VLF emission observation by Polar Patrol Balloons - Hisao Yamagishi; Taketoshi Miyake; Toshimi Okada; Akihiro Chino; Akira Kadokura; Yusuke Ebihara; Natsuo Sato; Hiroshi Takano (National Institute of Polar Research, 2006)
Circum-Antarctic balloons were launched from Syowa Station by the 44th Japanese Antarctic Research Experiment team in January 2003. Two balloons equipped with identical instruments were flown in formation around the Antarctic continent, in an attempt to separate temporal and spatial variations of the auroral phenomena. In this paper, we report instrument design, operation and some initial results of the ELF/VLF wave experiment by PPB No. 8 and 10 balloons.